THE EFFECT OF TOTAL QUALITY MANAGEMENT IMPLEMENTATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE (A Case Study At Spinning 1 Production Department PT. ApacInti Corpora) - Dian Ninta Desmanda; Noor - Suroija; Paniya - Paniya (JOBS (Jurnal Of Business Studies), 2017)
Global competition prompts businesses to improve the quality of their employee as the first value asset of an organization which can lead to achieve sustainability of business. This research examines the effect of total quality management implementation and work motivation on employee performance at Spinning 1 Production Department PT. ApacInti Corpora, Bawen, Semarang. Questionnaire is used as an instrument of primary data collection, which was distributed to 90 respondents. The method of this study is multiple regression analysis. The calculation result of the method shows that total quality management implementation and work motivation has positive and significant effect on employee performance and gave contribution to employee performance of 43% while 57% are influenced by other variables which are not described in this study.